Таксономічні та номенклатурні проблеми Bromus hordeaceus L. і B. mollis L. (Poaceae) - Красняк, О.І. (Український ботанічний журнал, 2012)
Рассмотрены главные проблемы в таксономии и номенклатуре Bromus hordeaceus и B. mollis.
Показаны основные события в процессах типификации и причины признания приоритета
B. hordeaceus. The most important issues on taxonomy and nomenclature of Bromus hordeaceus and B. mollis are
reviewed. The key typification stages and causes of priority acceptance of B. hordeaceus are shown.